Synthesis and characterization of novel polymer matrix composites reinforced with max phases (Ti3SiC2, Ti3AlC2, and Cr2AlC) or MoAlB by fused deposition modeling. Issue 3 (30th August 2019) - Hall, Kathryn; Dey, Maharshi; Matzke, Caleb; Gupta, Surojit
Abstract: In this paper, we report the synthesis and characterization of polylactic acid (PLA)‐MAX (Ti3 SiC2, Ti3 AlC2, and Cr2 AlC) and PLA‐MoAlB composites by fused deposition modeling (FDM). Detailed scanning electron microscopy (SEM) studies showed that the particulate phases are uniformly dispersed in the PLA matrix of 3D‐printed samples. Differential scanning calorimetry (DSC) results showed that the addition of MAX phases promoted crystallization of PLA matrix as compared to MoAlB particulates. The mechanical testing results showed that the PLA matrix is sensitive to the addition of MAX or MoAlB phases, for example, PLA‐5 wt% Ti3 SiC2, PLA‐5 wt% Ti3 AlC2, and PLA‐5 wt% Cr2 AlC had a UTS of ~39 MPa, ~30.5 MPa, and ~38.7 MPa as compared to ~41.5 MPa in pure PLA. Comparatively, PLA‐5 wt% MoAlB had a UTS of ~23.2 MPa which shows that predominantly amorphous PLA‐MoAlB composites have lower strength. The tribological behavior improved after the addition of 1 wt% additives, for example, in PLA‐Cr2 AlC, the friction coefficient decreased by 76% to ~0.26 from ~0.34 in pure PLA, and the WR marginally decreased in PLA‐1 wt% Cr2 AlC to ~2.2 × 10 −5  mm 3 /Nm as compared to 7.7 × 10 −5  mm 3 /Nm in PLA. SEM investigations of the tribosurfaces showed the tribology is governed by the formation of tribofilms. The wettability study showed that all the 3D‐printed samples are hydrophilic in nature. Abstract : In this paper, we report for the first time, the mechanical and tribological behavior of 3D‐printed PLA‐MAX composites. Detailed studies showed that MAX Phases can be used as additives for enhancing tribological behavior.